A new species of the waspfish genus Ocosia (Teleostei: Tetrarogidae) from the Coral Sea, with a key to species in the genus - Chungthanawong, Sirikanya; Motomura, Hiroyuki (Zootaxa, 2022)
The new waspfish Ocosia dorsomaculata n. sp. (Tetrarogidae) is described, based on specimens from Australia (5) and New Caledonia (51). Although O. dorsomaculata and Ocosia apia Poss & Eschmeyer 1975 both share modally XVI, 8 dorsal-fin rays with a long second dorsal-fin spine, and presence of supraocular, lateral lacrimal, and suborbital spines, the former has modally 13 pectoral-fin rays (vs. usually 12 in the latter), a lower modal count of total gill rakers (10 vs. 16–18), greater upper-jaw length, greater third to sixth dorsal-fin spine lengths, the third dorsal-fin spine slightly shorter than the second dorsal-fin spine (vs. third spine markedly shorter than second spine), 1 or 2 prominent pale brown to dark brown blotches on the membrane between the fifth to eighth or sixth to ninth dorsal-fin spines (vs. 1 blotch on the membrane around the third dorsal-fin spine and 1 blotch on the membrane between the sixth to eighth dorsal-fin spines), and body with 11–15 longitudinal pale brown to dark brown bars along lateral line (vs. irregular brown specks). A key to the species of Ocosia is given.